Morphological transparency and markedness matter in heritage speaker gender processing: an EEG study - Luque, Alicia; Rossi, Eleonora; Kubota, Maki; Nakamura, Megan; Rosales, César; López-Rojas, Cristina; Rodina, Yulia; Rothman, Jason (Frontiers in Psychology, 2023)
The present study investigated the qualitative nature of grammatical gender knowledge and processing in heritage speakers (HSs) of Spanish living in the United States. Forty-four adult Spanish HS bilinguals participated, completing a behavioral grammatical gender assignment task and a grammaticality judgment task (GJT) while their brain activity was recorded using electroencephalography (EEG). The EEG GJT task included grammatical and ungrammatical sentences with grammatical gender violations on inanimate nouns, where transparency of the morpho(phono)logical cue and markedness were manipulated. The results of this study revealed that grammatical gender violations elicited the typical P600 effect across all relevant conditions, indicating that the grammatical representations and processing of grammatical gender in HSs are qualitatively similar to those in Spanish-dominant native speakers. Given the experimental manipulation in this study, these findings also suggest that both morphological transparency and markedness play significant roles in how grammatical gender is processed. However, the results of this study differ from those reported in previous studies with Spanish-dominant native speakers, as the P600 effect found was accompanied by a biphasic N400 effect. This pattern of results is interpreted as further evidence that the bilingual experience of HSs modulates certain aspects of morphosyntactic processing, particularly conferring a greater reliance on morphology. Additionally, the results of this study highlight the importance of incorporating neurolinguistic online processing methods to better understand what underlies HS bilingual competence and processing outcomes.